ANENCEPHALIC FETUS WITH CRANIOSPINAL RACHISCHISIS – CASE REPORT - Konac, Ayse (International Journal of Research -GRANTHAALAYAH, 2021)
Anencephaly, in which a substantial part of the brain, skull, or scalp is missing, is a lethal neural tube defect (NTD) that occurs during the fourth week of pregnancy after failed cranial neuropore closure. One in every 1,000 births is anencephalic, and newborns with this NTD are not viable or treatable. Associated with anencephaly is rachischisis, or severe incomplete neural tube closure and exposure of the spinal cord. Ultrasonography can quickly diagnose anencephaly. Like other NTDs, nutritional and environmental factors both play a role in the development of anencephaly. Here, we report and discuss an unusual case of a 12-week gestation anencephalic fetus with craniospinal rachischisis and its embryological roots. In our case, except from the low socio-economic life of the patient, the absence of a predisposing factor that could cause such an anomaly, the abortion being in the first trimester and the occurrence in the first pregnancy of the patient as a result of 5-year infertility made us think that pathology examination of the abortus material is important in complet or incomplete abortions.